The root of friendship : self-love and self-governance in Aquinas - Flood, Anthony T. (Washington, D.C. : Catholic University of America Press, 2014)
The Root of Friendship addresses the connections between self-love and self-governance in the thought of Saint Thomas Aquinas and defends three related theses. First, Aquinas account of proper self-love is a description of the nature and importance of a persons subjective self experience. Second, his notion of self-governance cannot be under- stood fully unless we grasp its basis in self love. Finally, his account both satisfies contemporary conditions of relevance for self-governance and offers attractive solutions to issues raised in analytic discussions on such matters. Accordingly, the book provides a systematic account of Aquinas thoughts on the nature of a persons self-experience and the role that experience plays in self-governance.
Proper Self-Love and the Inner Life -- The Eudaimonist Self-Governance Tradition -- Persons, Providence, and the Natural Law -- Prudence and Pride -- Aquinas and Contemporary Criteria for Self-Governance -- Aquinas in Dialogue with Contemporary Accounts.
Includes bibliographical references and index.
Print version record.
Keywords: Thomas, -- Aquinas, Saint, -- 1225?-1274.; Self-acceptance.; Self-acceptance.; Thomas -- Aquinas, Saint -- 1225?-1274.; RELIGION -- Philosophy; PHILOSOPHY -- Ethics & Moral Philosophy; Thomas, -- Aquinas, Saint, -- 1225?-1274.; Self-acceptance.; Electronic books